1981
DOI: 10.1093/schbul/7.3.509
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Dual Level Word List on Schizophrenic Free Recall

Abstract: Three-category dual level, three-category single level, and six-category single level word lists were presented for single trial free recall to 18 normals and 18 schizophrenics in remission. Schizophrenic recall was significantly inferior to that of normals across all three lists. Normals produced more clustering than schizophrenics, but the difference was not significant. Across both groups, the three-category dual level list produced significantly more recall than the other two lists. The three-category dual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1983
1983
2003
2003

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Other component processes of memory, although not necessarily automatic, also appear normal, such as the rate of scanning items in short-term memory (reviewed in Broga and Neufeld 1981). In long-term memory, the semantic and syntactic ordering of representations also appears to be normal (Larsen and Fromholt 1976; Koh, Marusarz, and Rosen 1980; Broga and Neufeld 1981; Lutz and Marsh 1981). Recall, however, is impaired.…”
Section: Attention In Schizophreniamentioning
confidence: 99%
See 1 more Smart Citation
“…Other component processes of memory, although not necessarily automatic, also appear normal, such as the rate of scanning items in short-term memory (reviewed in Broga and Neufeld 1981). In long-term memory, the semantic and syntactic ordering of representations also appears to be normal (Larsen and Fromholt 1976; Koh, Marusarz, and Rosen 1980; Broga and Neufeld 1981; Lutz and Marsh 1981). Recall, however, is impaired.…”
Section: Attention In Schizophreniamentioning
confidence: 99%
“…The evidence suggests that while the structure of representations in the schizophrenic patient’s memory is intact, he has difficulty remembering things because of a defect in the controlled, attentional processes that make for efficient recall (Larsen and Fromholt 1976; Koh and Peterson 1978; Koh, Marusarz, and Rosen 1980; Broga and Neufeld 1981; Lutz and Marsh 1981). Without easy recourse to long-term memory, and without being able to shift attention further along to the next cognitive stages, the schizophrenic patient is at the receiving end of a volley of first impressions—and therefore at the mercy of a perception heavily influenced by old prejudices, attitudes, and momentary fears and expectations.…”
Section: The Experience Of Schizophreniamentioning
confidence: 99%
“…In the last decade the connection between these two ideas was made, and the schizophrenic verbal long-term memory deficit has been attributed to an associative or organizational disturbance, resulting in defective encoding (see reviews by Koh 1978;Neale and Oltmanns 1980). It has been shown that schizophrenics have the potential to use mnemonic organization effectively but fail to make full use of it at the encoding stage (Koh, Kayton, and Schwartz 1974;Traupmann 1980;Lutz and Marsh 1981). Support for an encoding failure, but no further disturbances, came from several sources.…”
mentioning
confidence: 99%